Respuesta :

Answer:

b = -2

Step-by-step explanation:

1) Cross multiply the proportion, in turn, you receive 2(b-4) = 6b.

2) Simply said equation, you should have 2b - 8 = 6b.

3) Subtract the 2b from each side, effectively canceling it out on the left (original position) and resulting in 6b to become 4b (6b - 2b = 4b).

4) After you have -8 = 4b, you can divide both sides by 4, canceling out on the right (original position).

5) You are finally left with -2 = b, reversing this results in b = -2.

-2 is your answer.